In vitro antibacterial, antifungal and skin cytotoxic activities of Alpinia javanica, A. galanga and A. conchigera - Khan, Farman Ullah (Kulliyah of Pharmacy, International Islamic University Malaysia, 2016)
The genus Alpinia belongs to the family of Zingiberaceae. It is distributed in tropical Africa, Asia, and particularly in Southeast Asia. The study was conducted to evaluate the antimicrobial and skin cytotoxic activities of Alpinia javanica, Alpinia galanga and Alpinia conchigera extracts. The crude extracts of A. javanica, A. galanga and A. conchigera were evaluated for their antimicrobial activity against human dermatophytes, gram positive and gram negative bacteria, and multidrug/methicillin resistant Staphylococcus aureus (MRSA) by using Disk Diffusion assay. Minimum inhibitory concentrations (MICs), minimum bactericidal and fungicidal concentrations (MBC and MFC) of A. javanica, A. galanga and A. conchigera crude extracts were determined based on a broth micro-dilution method in 96-microwell plates. The acetoxychavicol acetate (ACA), which is the major compound in Alpinia, was analysed and identified by using thin layer chromatography (TLC) and high performance liquid chromatography (HPLC). The toxic or hazardous effects of Alpinia extracts on normal mouse fibroblast (NIH/3T3) and normal human epidermal keratinocytes - adult (NHEK-a) cell lines were assessed through MTT assay. Overall, all extracts of A. javanica, A. galanga and A. conchigera showed good antibacterial and antifungal activities. However, hexane extract from A. javanica rhizome demonstrated strongest antibacterial activity with inhibition zone of 26 ± 0 mm against Staphylococcus aureus. In general, rhizome extracts of A. galanga showed strongest antibacterial effect as compared to leaf extracts. Overall, all Alpinia extracts showed good antibacterial activities against multidrug/methicillin-resistant Staphylococcus aureus (MRSA), however hexane extract from rhizome of A. javanica demonstrated strongest antibacterial activity against all strains of MRSA, followed by dichloromethane (DCM) and methanol extracts. The antibacterial activity of hexane extract was 29 ± 0.60 mm against MRSA. Similarly, A. javanica rhizome extracts demonstrated strongest antifungal activity against Microsporum canis. Antifungal activities of hexane extracts were 20 ± 0 mm and 21 ± 1.5 mm, against Trichophyton rubrum and M. canis respectively. All extracts of A. conchigera showed significant antifungal activities; however, compared to the A. javanica and A. galanga extracts, the inhibition is weaker. In MIC, MBC and MFC study, hexane and methanol extracts showed significant inhibitory effects as compared to DCM extract. According to TLC analysis, all hexane and methanol extracts of A. javanica, A. galanga and A. conchigera rhizome showed the presence of ACA at the Rf value of 0.61. HPLC analysis also confirmed the presence of ACA compound in all rhizomes extracts (except DCM) of A. javanica, A. galanga and A. conchigera. HPLC fingerprint showed identical ACA peak at retention time of 7.66 min (standard) and 7.66 min for hexane and methanol extracts of A. javanica, A. galanga and A. conchigera rhizome extracts. The present study showed that all extracts of A. javanica, A. galanga and A. conchigera were not toxic towards both NIH/3T3 and NHEK-a cell lines. In conclusion, the findings demonstrated that Alpinia could be a cheaper and feasible source to fight against pathogens that causes fungal skin infections such as tinea and MRSA infections but further research should be carried out on the isolation of specific bioactive compounds and their characterizations.